PROYEKSI KEBUTUHAN ENERGI LISTRIK KOTA PALU MENGGUNAKAN KONSEP LOGIKA FUZZY MAMDANI - Masarrang, Maryantho (-)
Long-term load forecasting is intended to estimate the electrical load on an annual time period. It has an important role in the real control and security functions of an energy management system. This study is focused on designing long-term load forecasting in Palu electrical systems by using mamdani fuzzy logic method. The process of long term load forecasting is done by providing inputs: the number of customers, PDRB, and the power used for residences, businesses and public load at the previous year into the fuzzy logic system so that it is produced an output: theÂ  power used for the next year. The result shows that mamdani fuzzy logic provide a high level accuracy of forecasting and very small value of MSE.